Enhancing durability of CIS43 monoclonal antibody by Fc mutation or AAV delivery for malaria prevention - Neville K. Kisalu; Lais D. Pereira; Keenan Ernste; Yevel Flores-Garcia; Azza H. Idris; Mangaiarkarasi Asokan; Marlon Dillon; Scott MacDonald; Wei Shi; Xuejun Chen; Amarendra Pegu; Arne Schön; et al. (JCI Insight, 2021)
CIS43 is a potent neutralizing human mAb that targets a highly conserved “junctional” epitope in the Plasmodium falciparum (Pf) circumsporozoite protein (PfCSP). Enhancing the durability of CIS43 in vivo will be important for clinical translation. Here, 2 approaches were used to improve the durability of CIS43 in vivo while maintaining potent neutralization. First, the Fc domain was modified with the LS mutations (CIS43LS) to increase CIS43 binding affinity for the neonatal Fc receptor (FcRn). CIS43LS and CIS43 showed comparable in vivo protective efficacy. CIS43LS had 9- to 13-fold increased binding affinity for human (6.2 nM versus 54.2 nM) and rhesus (25.1 nM versus 325.8 nM) FcRn at endosomal pH 6.0 compared with CIS43. Importantly, the half-life of CIS43LS in rhesus macaques increased from 22 days to 39 days compared with CIS43. The second approach for sustaining antibody levels of CIS43 in vivo is through adeno-associated virus (AAV) expression. Mice administered once with AAV-expressing CIS43 had sustained antibody levels of approximately 300 μg/mL and mediated protection against sequential malaria challenges up to 36 weeks. Based on these data, CIS43LS has advanced to phase I clinical trials, and AAV delivery provides a potential next-generation approach for malaria prevention.